Incidence and predictors of incisional hernia after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. (1st January 2019) - Tuttle, Todd M.; Huang, Jing Li; Kizy, Scott; Altman, Ariella M.; Nalluri, Harika; Marmor, Schelomo; Gaertner, Wolfgang B.; Jensen, Eric H.; Hui, Jane Y.C.
Abstract: Background and objectives: The incidence of incisional hernia (IH) after cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is largely unknown. Methods: We conducted a retrospective study to identify patients who underwent CRS/HIPEC from 2001 to 2016. Patients were followed postoperatively for a minimum of two years. The primary outcome was the occurrence of an IH identified either on CT scan or physical examination. Univariate and multivariable logistic regression models were used to test associations with IH. Results: We identified 155 patients who underwent CRS/HIPEC; 26 patients (17%) were diagnosed with an IH at a median time of 245 days (Interquartile range [IQR] 175 – 331 days). On multivariable analysis, older age [50–64 vs. 18–49 years: hazard ratio (HR) = 0.08; 95% confidence interval (CI), 0.01 to 0.64)], female gender (HR  =  0.09; 95% CI, 0.01 to 0.75), and increased BMI (>30 vs. <25; HR  =  0.03; 95% CI, 0.01 to 0.37) were significant independent predictors of IH. Conclusions: The incidence of IH in this high-risk patient population treated with CRS/HIPEC is similar to that after other abdominal cancer operations. Nevertheless, the occurrence of IH is an important patient outcome, so alternative closure techniques for reducing IH should be studied in this patient population. Synopsis: In a single-institutional study, the incidence of incisional hernia was 17% after cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy. Independent risk factors of incisional hernia were older age, female gender and obesity.